Reconciling opposing perceptions of access to physical activity in a gentrifying urban neighborhood. Issue 4 (25th March 2019) - Schroeder, Krista; Klusaritz, Heather; Dupuis, Roxanne; Bolick, Ansley; Graves, Amy; Lipman, Terri H.; Cannuscio, Carolyn
Abstract: Objective: We sought to understand perspectives on access to physical activity in a gentrifying neighborhood. Design: This qualitative descriptive study used street intercept interviews and photo documentation. Sample: Participants included members ( n  = 19) of a gentrifying neighborhood in a northeastern city. Results: Participants held markedly different perceptions of opportunities for physical activity. Some participants, particularly area university students or those who are identified as White, perceived the neighborhood as favorable to physical activity, with high walkability and abundant resources. Other participants, particularly those who identified as Black or African‐American, felt it was difficult to be physically active because neighborhood recreation facilities are scarce or unaffordable and parks are poorly maintained or unsafe. Multiple participants noted strategies to overcome neighborhood barriers to physical activity. Regardless of neighborhood perceptions, family and friends played an important role in influencing physical activity. Conclusions: Nurses must consider how disparities in actual and perceived access to neighborhood resources influence participation in physical activity, particularly in gentrifying neighborhood. Public health nurses are embedded in the neighborhoods that they serve, providing a unique opportunity to understand and address the impact of neighborhood on health.